2015
DOI: 10.3855/jidc.5415
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human cysticercosis and its associated risk factors among humans in areas of Kaduna metropolis, Nigeria

Abstract: Introduction: Taenia solium cysticercosis is considered an emerging parasitic zoonosis of global importance due to its impact on both agriculture and public health in developing countries. Epidemiological information on human cysticercosis is limited in Nigeria. This study was conducted to determine the seroprevalence of human cysticercosis in areas of Kaduna metropolis, Nigeria, where small-holder pig farming is practiced. Methodology: A cross-sectional survey was conducted in Kaduna South and Chikun Local Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 16 publications
1
22
1
4
Order By: Relevance
“…Eating of pork by someone with epilepsy promotes cysticercosis and corroborates with a study that found a significant link between cysticercosis occurrence and epilepsy [78]. In West Africa, T. s o l i u m cysticercosis in pigs and man has been reported and reports have shown the prevalence's of porcine cysticercosis across the west African countries varies from 0.05 to 46% for both carcass inspection and serological studies and prevalence of taeniid eggs were found to be between 8.6 and 40% based on stool microscopy while copro-antigen ELISA gave a prevalence of 30% [65] as shown in Tables 1 and 2. Difference in severity of infection caused by T. s o l i u m could also explain the differences in prevalence of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Eating of pork by someone with epilepsy promotes cysticercosis and corroborates with a study that found a significant link between cysticercosis occurrence and epilepsy [78]. In West Africa, T. s o l i u m cysticercosis in pigs and man has been reported and reports have shown the prevalence's of porcine cysticercosis across the west African countries varies from 0.05 to 46% for both carcass inspection and serological studies and prevalence of taeniid eggs were found to be between 8.6 and 40% based on stool microscopy while copro-antigen ELISA gave a prevalence of 30% [65] as shown in Tables 1 and 2. Difference in severity of infection caused by T. s o l i u m could also explain the differences in prevalence of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Abattoirs and approved slabs are the only approved places for slaughter and inspection of pork meat for consumption, however most carcasses are sold uninspected hence, lack of inspection and large scale clandestine slaughter of pigs promote spread of cysticercosis [32,34]. The poor knowledge of T. s o l i u m , poor hand washing practices, not treating drinking water and handling of raw pork with bare hands promote spread of cysticercosis [65]. Reports in the region indicate that home slaughter conditions were normally substandard because they are makeshift and not constructed to actually meet the requirements of ideal slaughter premises [48].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations